An H1-Galerkin Mixed Finite Element Approximation of a Nonlocal Hyperbolic Equation. Issue 5 (3rd September 2017) - Chen, Fengxin; Zhou, Zhaojie
Abstract: In this paper we investigate a semi-discrete H 1 -Galerkin mixed finite element approximation of one kind of nolocal second order nonlinear hyperbolic equation, which is often used to describe vibration of an elastic string. A priori error estimates for the semi-discrete scheme are derived. A fully discrete scheme is constructed and one numerical example is given to verify the theoretical findings.